Modeling Network Problem using Metric Dimension: Applied Algorithm on Corona Graph - Rahmadi, Deddy; Ramadhani, Ilma Nindita; Dheana, Clarissa Elva; Mustamin, Miftah Aulia (Mathematical Journal of Modelling and Forecasting, 2024)
Let G be a graph is a finite set of vertices and edges.  A graph G can be defined as a pair of sets . The minimum cardinality of all distinguishing sets in a graph is called the metric dimension. The metric dimension was first introduced in 1966 by Harary and Melter. The method used in this research is deductive proof. The results obtained from this research are we determine the metric dimension of the graph resulting from the corona operation on  and obtain the result that is 2n.